2013
DOI: 10.1111/jnu.12010
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Interventions for Nipple Trauma in Breastfeeding Mothers

Abstract: This study provides evidence for nursing practice, thus contributing to the improvement of lactating mothers with nipple trauma care and, consequently, improving the rates of successful breastfeeding as well as the quality of life of breastfeeding mothers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 20 publications
1
49
1
3
Order By: Relevance
“…1 The use of products for prevention of nipple fissure is not useful and could be counterproductive. 1,19 Many studies 11,12,35 on the prevention and treatment of nipple fissures and mammary lesions in the course of nursing had an inadequate sample size, and most, as well, showed bias.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1 The use of products for prevention of nipple fissure is not useful and could be counterproductive. 1,19 Many studies 11,12,35 on the prevention and treatment of nipple fissures and mammary lesions in the course of nursing had an inadequate sample size, and most, as well, showed bias.…”
Section: Discussionmentioning
confidence: 99%
“…These include topical creams, solutions, or sprays, time-restricted breastfeeding, exposure of the nipple to dry heat or ultraviolet light and air-drying, pre-or postnatal breastfeeding education, breast protection shells, hydrogel, adhesive polyethylene film dressing, and distilled water. 6,[11][12][13] A recent systematic review by Vieira et al 11 on the several interventions for nipple trauma in breastfeeding mothers concluded that the best outcomes for the treatment of nipple trauma used lanolin (recommendation B, evidence level 2) and breastmilk (recommendation B, evidence level 2). However, the biggest study on 225 puerperal mothers by Mohammadzadeh et al, 14 cited in this review, questioned the efficacy of lanolin and highlighted the superiority of breastmilk.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…In contrast, two of the remaining reasons -'My baby had trouble sucking or latching on' and 'My nipples were sore, cracked or bleeding' -are acute breast-feeding management issues most likely to occur during the early phases of lactation, which may be addressed by skilled health professional intervention at that time. [38][39][40] Biting behaviour in infants was included among the four most commonly cited reasons for breastfeeding cessation only in the sample between 6 and 11 months of infant age. A recent study 24 provided 'perception of insufficient milk' as a response option instead of 'I did not have enough milk'.…”
Section: Discussionmentioning
confidence: 99%